A scoping review of education and training interventions in Autism Spectrum Disorder. Issue 9 (September 2022) - Morsa, Maxime; De Andrade, Vincent; Alcaraz, Céline; De La Tribonnière, Xavier; Rattaz, Cécile; Baghdadli, Amaria
Abstract: Objective: Autism Spectrum Disorder (ASD) is a chronic neurodevelopmental disorder. Living with ASD requires that individuals and parents develop skills in order to cope with daily life. Education interventions are recommended to support them. This study aims to get an overview of education and training interventions in ASD. Methods: A scoping review of international literature was conducted. Results: 43 articles were analyzed. Four main types of intervention stand out: support groups, parental training; psychoeducation; therapeutic patient education. However, the majority of publications is focused on the parents rather than on individuals living with ASD, and the needs assessments identified focused on general needs rather than educational needs. Conclusion: While educational interventions for parents and individuals with ASD are now encouraged, considerable heterogeneity is observed. But this variety is not based on a reasoned approach to matching supply and needs. Future studies could focus more on the educational needs of individuals with ASD. Practice implications: Overview of education and training interventions in ASD help health care providers to better understand the strengths and limitations of their interventions. Highlights: Support and counseling, parental training, psychoeducation and therapeutic patient education are the four main types of intervention. Studies are mainly focused on parents. There is a lack of knowledge on educational needs.